Analysis of Twitter Social Media Framing in the New Normal Era (Case Study of Malang City Tourism Promotion) - Ramang H Demolingo; Reza Emelia; Kumba Digdowiseiso (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the framing of Twitter social media in an effort to promote tourism by the Malang City government in the New Normal era. The research method used in this research is a qualitative research method with a case study approach. By using the NVivo 12 Plus software as a Qualitative Data Analysis Software (QDAS) that utilizes the Crosstab analysis and Word Frequency Analysis features to conduct data mining and analysis on the official twitter account of the Malang city government, namely @PemkotMalang. Departing from the theory of Integrated Marketing Communication which is divided into 4 dimensions, namely; planning, creation, integration, and marketing. Based on the findings and analysis of the researchers, it can be concluded that the Malang City government uses a strategy of delivering information through social media Twitter @ PemkotMalang consistently mapped to the IMC concept, which contains several aspects, namely planning, creation, integration, and marketing. Of the four aspects, creation dominates because it includes content that changes tourism marketing in Malang City. The information conveyed was in the form of implementing new policies in the tourism sector to recover after the COVID-19 pandemic. As for other complementary aspects, such as the planning aspect, Malang City prepares facilities that meet health protocols so that tourists feel safe and increase their trust when visiting tourist objects in Malang City.